Correlation Between Learning Outcomes and Students' Science Process Skills in Class X Biology Material at SMA Negeri 9 North Luwu - Dewi Kusumawati; Nurhayati; Hartati (Indonesian Journal of Biology Education, 2024)
This research aims to determine the relationship between learning outcomes and students' science process skills in class X biology material at SMA Negeri 9 North Luwu. This type of research is descriptive correlational research. The population in this study were all class X students at SMA Negeri 9 North Luwu, with a research sample of 73 students. The data collection technique uses a scientific process skills observation sheet consisting of 10 aspects: observing, grouping, interpreting, predicting, asking questions, formulating hypotheses, planning experiments, using tools and materials, applying concepts, and communicating and testing learning outcomes. The data analysis used in this research is correlation analysis. The results of the research show that the learning outcomes of class Based on the research results, it was concluded that there is a strong and positive correlation between science process skills and student learning outcomes in environmental change material for class X SMA Negeri 9 North Luwu.